2006
DOI: 10.1039/b517523b
|View full text |Cite
|
Sign up to set email alerts
|

REMPI-TOF studies of the translational anisotropy and the polarization of the O (1D2) photofragment angular momentum following ozone photolysis at 298 nm

Abstract: The translational anisotropy and the polarization of the electronic angular momentum of the O ((1)D2) fragment produced from the 298 nm photodissociation of ozone have been determined using resonance enhanced multiphoton ionization (REMPI) in conjunction with time-of-flight mass spectrometry (TOFMS). The translational anisotropy parameter beta, which is necessarily averaged over the O2 co-fragment rotational distribution, is measured to be 1.08 +/- 0.04. This is consistent with that expected for the (1)B2 <-- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…I B, an experimental study of the orientation of O (1D 2) subsequent to excitation into the Hartley band at wavelengths between 248 and 285 nm has 23 recently been undertaken by Lee et al These experiments revealed a significant, speed-dependent y 1 ' parameter, which on average is about a factor of 10 higher than we observe at 193 nm but is of the same sign. The newer work at 298 nm by Denzer et al 25 yields a similar y1 parameter to those 23 obtained by Lee et al, if the latter are averaged over recoil speed. Furthermore, once the y 1 ' parameters are transformed into the molecular frame, they also agree well with the pre dicted orientation generated from the state of 1A symmetry at linearity that we have derived above from the long range model.…”
Section: E the K =1 Orientation Momentssupporting
confidence: 63%
“…I B, an experimental study of the orientation of O (1D 2) subsequent to excitation into the Hartley band at wavelengths between 248 and 285 nm has 23 recently been undertaken by Lee et al These experiments revealed a significant, speed-dependent y 1 ' parameter, which on average is about a factor of 10 higher than we observe at 193 nm but is of the same sign. The newer work at 298 nm by Denzer et al 25 yields a similar y1 parameter to those 23 obtained by Lee et al, if the latter are averaged over recoil speed. Furthermore, once the y 1 ' parameters are transformed into the molecular frame, they also agree well with the pre dicted orientation generated from the state of 1A symmetry at linearity that we have derived above from the long range model.…”
Section: E the K =1 Orientation Momentssupporting
confidence: 63%
“…The velocity-averaged values of Im͓a 1 1 ͑ ʈ , Ќ ͔͒ obtained here at 248 nm are similar in magnitude to those observed by Lee et al at 193 nm. 26,28,42,60,61 With one exception, 28 these studies returned zero 42,60 or small 26 values for the in-plane orientation moments. In the past, the possibility of static coherence arising from excitation to the 2 1 AЈ surface was discounted on the basis of the small perpendicular projection of the transition dipole moment on the recoil axis.…”
Section: E Orbital Orientationmentioning
confidence: 84%
“…ozone | photochemistry | quantum dynamics | isotopic fractionation | lambda doublets G iven the importance of the stratospheric ozone layer in protecting the earth from harmful ultraviolet (UV) rays (1), it is not surprising that the UV photodissociation of ozone has been the subject of numerous experimental (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and theoretical studies (16)(17)(18)(19)(20)(21)(22)(23)(24). In the strongly absorbing Hartley band (200-300 nm), the photodissociation involves two low-lying excited states with the same symmetry (A′) as the ground state (X): the B state which diabatically correlates to O 2 (a 1 Δ g ) and O( 1 D) products, and the R state which diabatically correlates to O 2 (X 3 Σ − g ) and O( 3 P) products.…”
mentioning
confidence: 99%